Pengaruh Likuiditas, Solfabilitas, Aktivitas Terhadap Profitabilitas Pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia (BEI) - Sabrina Nova Ashara; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2024)
Financial ratios are an analytical method used to measure and compare the relationship between various items in the financial statements of a company or business entity. Financial ratios are useful for evaluating financial health. Ratios such as liquidity ratios, profitability, and leverage are used to assess how well a company can fulfill its obligations, generate profits, and manage debt. Making investment decisions, investors use financial ratios to assess whether investing in shares or company bonds is a smart choice. Know the company's opportunities and risks in the future. The opportunity factor in financial ratios will influence investors' expectations of the company in the future. The aim of the research is to investigate and identify the extent to which liquidity, solvency and activity have an influence on the profitability of food companies listed on the Indonesia Stock Exchange (BEI). Thus, this research aims to provide a better understanding of the financial factors that influence the performance of food and beverage companies on the Indonesian stock market and how these variables are related to each other.